Макс Вебер о роли права в становлении рыночного капитализма - Бутусова, Н. (Социология: теория, методы, маркетинг, 1999)
The essay discusses Weber’s sociology of law, which is an essential part of his theoretical heritage, and also Weber’s analysis of relations between formal kinds ofrationality in law, economy and administration. Weber’s typology of legal thought forms is analyzed in its relation to domination forms typology. The author focuses onhistorical conditions of emerging formal rational law being essential to bringing about market capitalism. There have been presented how Weber had solved the England Problem and Weber’s prognosis about the further rationalization of law in accordance to the tends of law re-materialization.